The impact of gamification on English vocabulary learning among middle basic education students at a public institution in Loja city, school year 2022-2023. El impacto de la gamificación en el aprendizaje del vocabulario de inglés en los estudiantes de educación media en una institución pública de la ciudad de Loja, año lectivo 2022-2023. - Irene Gualan, Karol Estefania (2023)
Vocabulary has become a fundamental component of English language learning. Therefore, it is essential to apply strategies that help students learn vocabulary in an effective and enjoyable way. For this reason, this study aimed to determine the improvement of English vocabulary learning through the use of gamification, as well as to determine the possible strategies and activities to achieve an improvement in students' academic performance. A mixed method and action research design was used to collect quantitative and qualitative data through a pre-test, a post-test, a questionnaire and field notes. M, descriptive statistics helped to interpret the numerical data. On the other hand, the main results of the pre-test and post-test highlight the significant differences that were identified in the students' vocabulary level scores, considering vocabulary aspects such as form, meaning and shape, before and after the intervention time. Similarly, the questionnaire results show the students' positive perceptions regarding the use of gamification for English vocabulary learning and improvement. The main conclusions of this study highlight that the implementation of gamification has achieved an improvement in English vocabulary learning and provides activities that help students learn in an interactive environment. Keywords: English learning, gamification, gamified strategies, vocabulary